2017
DOI: 10.1002/jbm.b.33930
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel bioactive glass suitable for osteosarcoma‐related bone grafts

Abstract: In this study, zinc borate-based glasses with increasing gallium content (0, 2.5, 5, 10, and 15 wt % Ga) were synthesized and their effect on the viability and proliferation of preosteoblasts and osteosarcoma cancer cells were investigated. Methyl thiazolyl tetrazolium (MTT) cell viability assays using glass degradation extracts revealed that the extracts from glasses with lower Ga contents could enhance the viability of preosteoblasts, while extracts from the glass composition with 15 wt % Ga caused statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…This is important to prevent thermal stresses between the glass coatings and this alloy when used in medical implants, which is common.Gallium oxide has been explored as an additive to zinc borate bioactive glasses to confer them with antibacterial properties [199]. The same authors also investigated the suitability of gallium-releasing zinc borate bioactive glasses for osteosarcoma-related bone graft operations using MTT and live/dead assay [200]. They concluded that glass powders containing 5 wt.% of Ga 2 O 3 could enhance the viability of preosteoblasts while reducing that of osteosarcoma cells.…”
Section: Bioactive Glasses and Glass-ceramicsmentioning
confidence: 99%
“…This is important to prevent thermal stresses between the glass coatings and this alloy when used in medical implants, which is common.Gallium oxide has been explored as an additive to zinc borate bioactive glasses to confer them with antibacterial properties [199]. The same authors also investigated the suitability of gallium-releasing zinc borate bioactive glasses for osteosarcoma-related bone graft operations using MTT and live/dead assay [200]. They concluded that glass powders containing 5 wt.% of Ga 2 O 3 could enhance the viability of preosteoblasts while reducing that of osteosarcoma cells.…”
Section: Bioactive Glasses and Glass-ceramicsmentioning
confidence: 99%
“…Cell viability assays using 3‐(4,5‐dimethylthiazolyl‐2)‐2,5‐diphenyltetrazolium bromide (MTT) assay kits were performed to determine in vitro cytotoxicity of the borate‐based glass scaffolds (Rahimnejad Yazdi, Torkan, Waldman, & Towler, 2018). Pre‐osteoblastic MC3T3‐E1 (ATCC CRL‐2593) cells and glass scaffold degradation extracts were used.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence‐based live‐dead assay (Molecular Probes Inc. OR) with calcein AM for labeling live cells and EthD‐1 for labeling dead cells were used to evaluate the viability of the pre‐osteoblastic MC3T3‐E1 (ATCC CRL‐2593) cells after exposure to glass scaffold degradation extracts (Rahimnejad Yazdi et al, 2018). Similar to MTT assay, pre‐osteoblastic cells were cultured in minimum essential medium (MEM) α supplemented with 10% fetal bovine serum and 1% antibiotic–antimycotic and maintained in a cell culture incubator for 24 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased osteosarcomas viability using containing 5% wt. Ga 2 O 3 glass extract for 7 days [ 91 ] B 2 O 3 –CaO–Na 2 O–K 2 O–MgO–P 2 O 5 –Ce 2 O 3 (1, 3, 5%)/Ga 2 O 3 (1, 5%) Characterization of scaffold and powder by SEM-EDX, XRD, FTIR, DTA-TG. In vitro bioactivity and degradation studies in SBF.…”
Section: Gallium In Bioactive Glassesmentioning
confidence: 99%
“…A borate glass system (B 2 O 3 –Na 2 O–CaO–P 2 O 5 –ZnO-Ga 2 O 3 ) incorporating up to 16 wt % of gallium was investigated by Yazdi et al [ 91 ]. Degradation rate and weight loss of the glass in deionized water were reduced with gallium addition: it followed to changes in the glass network, where gallium substituted boron [ 92 ].…”
Section: Gallium In Bioactive Glassesmentioning
confidence: 99%